Selection of early‑maturing sweet orange cultivars by performance indexes - Caputo, Marina Maitto; Mourão Filho, Francisco de Assis Alves; da Silva, Simone Rodrigues; Bremer Neto, Horst; Couto, Hilton Thadeu Zarate do; Stuchi, Eduardo Sanches (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to select adequate early‑maturing sweet orange cultivars for the fresh fruit market and for industrial processing using performance indexes. Performance indexes for citrus were established from data collected in an experiment carried out in the southwest region of the state of São Paulo, involving 12 early-maturing sweet orange cultivars. New results were obtained by identifying cultivars with superior characteristics. In a comparison with ’Hamlin’ sweet orange, a standard early-maturing cultivar, ’Valência 2’ and ’Salustiana’ were considered better materials for the fresh fruit market, whereas ’Westin’ sweet orange was identified as a superior cultivar for orange juice processing.